Special Consideration in Post-Secondary Institutions: Trends at a Canadian University - Zimmermann, Joelle; Kamenetsky, Stuart B; Pongracic, Syb (Canadian Journal of Higher Education, 2015)
This study examined trends in the practice of granting special consideration for missed tests and late papers in colleges and universities. We analyzed a database of 4,183 special consideration requests at a large Canadian university between 1998 and 2008. Results show a growing rate of requests per enrolment between 2001 and 2007. Although university officials and faculty are concerned that request making is excessive, an in-depth investigation of request making by the number of requests per student, request rate by course difficulty, grade point average, and illness-related work absences in the general population fails to support suspicions of dishonest behaviour. Furthermore, demographic variables—aside from part-time versus full-time student status, and to a lesser degree socio-economic status—do not distinguish students who made frequent requests from those who made few. We discuss potential explanations for the increase in requests for special consideration.